SPINAL ANATOMY AND BEYOND: INVESTIGATING DEGENERATIVE DISC DISEASE - KHAN , QUA; MALIK , F; REHMAN , A; NAQVI , SAZ; AZHAR, F (Biological and Clinical Sciences Research Journal, 2024)
Degenerative disc disease is a common manifestation in routine spine imaging; this finding is partly attributable to physiological aging and partly to a pathological condition, and sometimes, this distinction is simply not clear. The study’s main objective is to find the spinal anatomy and investigate degenerative disc disease in spinal patients. This mixed-methods study was conducted in a public hospital in Karachi, Pakistan from March 2023 to September 2023. Fifty patients diagnosed with DDD are enrolled, with comprehensive clinical assessments conducted to evaluate symptomatology, functional impairment, and radiological findings. Additionally, advanced imaging modalities, including MRI and CT scans, elucidate structural changes within the spinal column. Preliminary analysis reveals a mean disc height loss of 3.2 mm (±0.8) across the study cohort, with significant variability observed among individual patients. Annular tears are prevalent in 70% of cases, predominantly localized to the lumbar spine. Furthermore, facet joint degeneration is evident in 85% of patients, with a mean grade of 2.4 (±0.6) on the Pfirrmann scale. Correlation analysis demonstrates a moderate positive correlation (r = 0.56, p < 0.001) between disc height loss and severity of clinical symptoms. It is concluded that this study provides the complex pathology of degenerative disc disease (DDD) and its impact on spinal anatomy. Through a comprehensive investigation involving clinical assessments and advanced imaging techniques, we have elucidated the spectrum of degenerative changes within the intervertebral discs and facet joints.